Drawing type : an introduction to illustrating letterforms - Fowkes, Alex, ....- (Beverly (Mass.) : Rockport Publishers, 2014)
Part inspiration and part workbook, these hand-drawn type of images will inspire and excite any designer to draw and explore type. Drawing Type features real-world projects and sketchbooks of well-known type designers, including interviews about their processes. Playful, hand-drawn type can easily be used in a range of disciplines within design and illustration such as packaging, editorial, posters, advertising, online graphics, and signage; the hand-made aesthetic is more prevalent now than ever. Alex Fowkes will help you to create custom lettering and typographic layouts. Alex encourages you to start drawing all kinds of typography, including serifs, sans serifs, and scripts. He provides ample examples of typefaces to draw inspiration from so you can become confident enough to draw your own. Drawing Type is perfect for learning and developing your skills at home or in a classroom--an invaluable resource that you can refer to again and again!